2019
DOI: 10.1093/toxsci/kfz054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Polybrominated Diphenyl Ethers (BDE-47, BDE-100, and BDE-153) in Human Breast Cancer Cells and Patient-Derived Xenografts

Abstract: Polybrominated diphenyl ethers (PBDEs) have been used as flame retardants in household materials. Their environmental persistence has led to continuous human exposure and significant tissue levels. Three PBDE congeners (BDE-47, BDE-100, and BDE-153) have been frequently detected in human serum. Although these compounds appear to possess endocrine disrupting activity, studies are largely missing to determine the biological mechanisms of PBDEs in breast cancer cells. Here, we assessed PBDE bioactivities with thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Additionally, BDE-47 had no effect on ERK phosphorylation in the two cell lines (25). In contrast, Kanaya et al recently reported that BDE-47 stimulated proliferation of an estrogen-dependent breast cancer cell line MCF-7aroERE and induced ER-regulated genes expression, which suggested that BDE-47 acted as a weak agonist of both ERα and estrogen-related receptor α (ERRα) (32). One previous case-control study from our laboratory demonstrated that BDE-47 level was positively with breast-cancer risk regardless of ER stratification (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, BDE-47 had no effect on ERK phosphorylation in the two cell lines (25). In contrast, Kanaya et al recently reported that BDE-47 stimulated proliferation of an estrogen-dependent breast cancer cell line MCF-7aroERE and induced ER-regulated genes expression, which suggested that BDE-47 acted as a weak agonist of both ERα and estrogen-related receptor α (ERRα) (32). One previous case-control study from our laboratory demonstrated that BDE-47 level was positively with breast-cancer risk regardless of ER stratification (33).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration used in this BDE-47 exposure model is based on the dose-response experiment and the data shown previously in other in vitro systems (34, 5052). Recently, Kanaya compared with in vitro breast cancer cell culture treatment at dosage of 10 μM to the published human serum/tissue concentrations of PBDEs (BDE-47 included), and concluded that the maximum concentrations observed in human serum and tissue concentrations were ~1,300 and 350 times lower than 10 μM, respectively (32). Therefore, future study will be needed to advance understanding the effect of environmentally relevant low-dose PBDEs on the progression and chemoresistance of EC cells in vitro and in vivo , which will help to answer the critical question whether real-life BDE-47 exposure could be a risk of human EC and resistance factor for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…To replicate physiologically relevant exposures, we assessed the relationship between dosage and both the ratio and murine sera levels of the three PBDEs congeners. The ratio was adjusted to reflect human exposure of three major PBDEs detected 47 . Compared to the highest concentration scenario in human exposure (i.e., maximum observed serum concentration), the mouse serum concentration in this study was 10–30 times higher than human exposure 47 .…”
Section: Methodsmentioning
confidence: 99%
“…The ratio was adjusted to reflect human exposure of three major PBDEs detected 47 . Compared to the highest concentration scenario in human exposure (i.e., maximum observed serum concentration), the mouse serum concentration in this study was 10–30 times higher than human exposure 47 . After one-week of treatment, mice were euthanized to collect blood and mammary glands.…”
Section: Methodsmentioning
confidence: 99%
“…The capability for scRNAseq to capture high-resolution transcriptional data also allows for profiling of cell populations by utilizing differentially expressed genes as signatures for gene ontology scoring. This method opens possibilities into identifying subpopulations based on function rather than comparison with gene lists in literature (13,14). Another emerging method used to analyze single cell data is through mapping ligand-receptor relationships at the cellular level.…”
Section: Overview Of Single Cell Rna Sequencingmentioning
confidence: 99%